FACTORS DETERMINING THE USE OF MOBILE BANKING IN INDONESIA - Shafa Aqilah; Muhammad Anwar Fathoni (The International Journal of Banking and Finance, 2023)
This study was aimed at determining the factors that could influence a person’s decision to use mobile banking. In this study, perceived usefulness, perceived ease of use, and perceived credibility were considered exogenous variables, and social factors as mediators. This research used quantitative methods. The population in this study were Indonesian Sharia Bank customers who used BSI mobile banking services in the Jakarta, Bogor, Depok, Tangerang and Bekasi areas. A sample of 200 people was obtained using the purposive sampling method. The analysis technique used was the inner model, outer model, and hypothesis testing using SmartPLS 3.2.9. The results obtained in this study showed that perceived usefulness had a significant effect on decisions to use mobile banking, perceived ease of use had no significant effect, and perceived credibility had a significant effect. In addition, this study has also shown that social factors did not succeed in mediating other variables in the decision to use mobile banking.